Ghost whisperer Season 5 discs 1 & 2 - Hewitt, Jennifer Love, 1979-; Conrad, David, 1967-; Manheim, Camryn; Kennedy, Jamie, 1970-; ABC Studios; CBS Studios Inc.; CBS DVD (Firm); Paramount Home Entertainment (Firm) ([Hollywood, Calif.] : CBS DVD : Paramount Home Entertainment, 2010)
Melinda Gordon has chilling, heart-stopping, amusing and emotional encounters with ghosts and those they haunt. At the tense intersection of the Living and the Dead, there is a mind-bending mystery that puts Melinda in lethal jeopardy--but also brings hope and miracles. Melinda's husband Jim is now a practicing physician at Grandview's haunted hospital. With the spirit world growing stronger, Melinda and Jim must find a way to balance their romance, and the challenges of the churning spirit world. Melinda comes to understand that her unique gift is a responsibility that must be honored to help souls in need--alive or dead--find perfect closure.
Disc 1. Birthday presence ; See no evil ; Till death do us start ; Do over -- disc 2. Cause for alarm ; Head over heels ; Devil's bargain ; Dead listing.
Part 1 of 3.
Title from container.
Originally broadcast on television during the 2009-2010 season.
Set includes all 22 episodes from the fifth and final season.
Jennifer Love Hewitt, David Conrad, Camryn Manheim, Jamie Kennedy.
MPAA rating: Not rated; CHV rating: PG.
Keywords: Mediums -- Drama; Ghost plays; Spirits -- Drama; Spiritualism -- Drama; Supernatural -- Drama; Businesswomen -- Drama; Spouses -- Drama; Drama; Fantasy television programs; Ghost television programs; Television programs; Television programs for the hearing impaired